Effects of the Reagent Rotational Excitation on the Stereodynamics of the Reaction $C(^3P)+CH(X^2Π)→C_2+H$ (Journal of Atomic and Molecular Sciences, 2015)
Based on the 1²A" global three-dimensional adiabatic potential energy surface[Boggio-Pasqua et al., Phys Chem. Chem. Phys 2:1693-2000], a theoretical studyof the stereodynamics of the reaction $C(^3P)+CH(X^2Π) (v=0; j=0$-$6)$ has been performedusing the quasi-classical trajectories(QCT) method. The cross sections are caculated.The differential cross sections (DCSs) and the distributions of $P(θ_r),$ $P(φ_r)$ are pensentedin detail at the selected collision energy of 0.3 eV. The product rotational alignment parameter $$ are also obtained as a function of the regent rotational quantumnumber. The results show that the reagent rotational excitation plays an important rolein the title reaction.
Keywords: stereodynamics; QCT method; rotation excitation; rotational alignment; reaction mechanism.